2007
DOI: 10.1007/s00424-007-0338-8
|View full text |Cite
|
Sign up to set email alerts
|

Locus coeruleus noradrenergic neurons and CO2 drive to breathing

Abstract: The Locus coeruleus (LC) has been suggested as a CO(2) chemoreceptor site in mammals. In the present study, we assessed the role of LC noradrenergic neurons in the cardiorespiratory and thermal responses to hypercapnia. To selectively destroy LC noradrenergic neurons, we administered 6-hydroxydopamine (6-OHDA) bilaterally into the LC of male Wistar rats. Control animals had vehicle (ascorbic acid) injected (sham group) into the LC. Pulmonary ventilation (plethysmograph), mean arterial pressure (MAP), heart rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
175
2
15

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(209 citation statements)
references
References 70 publications
17
175
2
15
Order By: Relevance
“…The LC neurons are CO 2 chemosensitive (Erlichman et al 2009;Johnson et al 2008;Oyamada et al 1998;Pineda and Aghajanian 1997;Stunden et al 2001). These norepinephrinergic (NE) neurons modulate firing activity of brain stem respiratory neurons (Biancardi et al 2008). Breathing activity is affected by local injection of NE to the pedunculopontine tegmental nucleus (Saponjic et al 2005).…”
mentioning
confidence: 99%
“…The LC neurons are CO 2 chemosensitive (Erlichman et al 2009;Johnson et al 2008;Oyamada et al 1998;Pineda and Aghajanian 1997;Stunden et al 2001). These norepinephrinergic (NE) neurons modulate firing activity of brain stem respiratory neurons (Biancardi et al 2008). Breathing activity is affected by local injection of NE to the pedunculopontine tegmental nucleus (Saponjic et al 2005).…”
mentioning
confidence: 99%
“…As in mammals, more than 80% of LC neurons in bullfrogs are CO 2 activated , reinforcing its importance as a site for central chemoreception in anurans (Noronha-de-Souza et al, 2006). Furthermore, given the similarities between LC responses in anurans and mammals in which focal acidification of the LC region stimulates ventilation and ablation reduces CO 2 -induced increases in ventilation in in vivo experiments (Biancardi et al, 2008;Noronha-de-Souza et al, 2006), it is clear that the LC has an analogous role, and possibly a homologous role, in respiratory control in terrestrial vertebrates. The present study provides data showing that the LC in the savannah monitor lizard is also chemosensitive within a normal, physiological range of pH/P CO2 , containing excited, inhibited and non-chemosensitive neurons, albeit in different proportions from those in rats and bullfrogs.…”
Section: Discussionmentioning
confidence: 86%
“…Nevertheless, at least one chemosensitive region, the locus coeruleus (LC), has been described in amphibians (toads and bullfrogs: Noronha-de-Souza et al, 2006; and mammals (reviewed in Gargaglioni et al, 2010), suggesting that CO 2 /pH chemosensitivity of the LC may be conserved across air-breathing vertebrates. Anatomical studies have identified noradrenergic cells of the LC in a variety of reptiles (Kiehn et al, 1992;Lopez et al, 1992;Smeets and González, 2000;Wolters et al, 1984), including savannah monitor lizard brainstems (Wolters et al, 1984), showing tyrosine hydroxylase-containing cell bodies in the LC neurons as observed in anurans and rats (Biancardi et al, 2008;Noronha-de-Souza et al, 2006).…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, knockout PHOX2B mice demonstrate in the central nervous system an underpopulation of noradrenergic neurons in the locus coeruleus and cellular anomalies of the nucleus of the solitary tract, i.e., abnormalities which require microscopic examination, including with neurotransmitter-specific immunocytochemistry, to detect (13). Of note, the locus coeruleus and nucleus of the solitary tract are both regions known to be chemosensitive to carbon dioxide (14,15). The murine abnormalities in the locus coeruleus and nucleus of the solitary tract are potentially below the resolution of DTI and still may occur in the present CCHS cases, but autopsy confirmation is required.…”
Section: Ongenital Central Hypoventilation Disorder (Cchs) Is Amentioning
confidence: 99%